The RATPAC (Randomised Assessment of Treatment using Panel Assay of Cardiac markers) trial: a randomised controlled trial of point-of-care cardiac markers in the emergency department - Steve Goodacre; Mike Bradburn; Patrick Fitzgerald; Elizabeth J. Cross; Paul Collinson; Alasdair Gray; Alistair S. Hall (2011)
To evaluate the clinical effectiveness and cost-effectiveness of using a point-of-care cardiac marker panel in patients presenting to the emergency department (ED) with suspected but not proven acute myocardial infarction (AMI). Multicentre pragmatic open randomised controlled trial and economic evaluation. Six acute hospital EDs in the UK. Adults presenting to hospital with chest pain due to suspected but not proven myocardial infarction, and no other potentially serious alternative pathology or comorbidity. Participants were allocated using an online randomisation system to receive either (1) diagnostic assessment using the point-of-care biochemical marker panel or (2) conventional diagnostic assessment without the panel. All tests and treatments other than the panel were provided at the discretion of the clinician. The primary outcome was the proportion of patients successfully discharged home after ED assessment, defined as patients who had (1) either left the hospital or were awaiting transport home with a discharge decision having been made at 4 hours after initial presentation and (2) suffered no major adverse event (as defined below) during the following 3 months. Secondary outcomes included length of initial hospital stay and total inpatient days over 3 months, and major adverse events (death, non-fatal AMI, life-threatening arrhythmia, emergency revascularisation or hospitalisation for myocardial ischaemia). Economic analysis estimated mean costs and quality-adjusted life-years (QALYs), and then estimated the probability of cost-effectiveness assuming willingness to pay of £20,000 per QALY gained. We randomised 1132 participants to point of care and 1131 to standard care, and analysed 1125 and 1118, respectively [mean age 54.5 years, 1307/2243 (58%) male and 269/2243 (12%) with known coronary heart disease (CHD)]. In the point-of-care group 358/1125 (32%) were successfully discharged compared with 146/1118 (13%) in the standard-care group [odds ratio (OR) adjusted for age, gender and history of CHD 3.81; 95% confidence interval (CI) 3.01 to 4.82, p < 0.001]. Mean length of the initial hospital stay was 29.6 hours versus 31.8 hours (mean difference = 2.1 hours; 95% CI -3.7 to 8.0 hours, p = 0.462), while median length of initial hospital stay was 8.8 hours versus 14.2 hours (p < 0.001). More patients in the point-of-care group had no inpatient days recorded during follow-up (54% vs 40%, p < 0.001), but mean inpatient days did not differ between the two groups (1.8 vs 1.7, p = 0.815). More patients in the point-of-care group were managed on coronary care [50/1125 (4%) vs 31/1118 (3%), p = 0.041]. There were 36 (3%) patients with major adverse events in the point-of-care group and 26 (2%) in the standard-care group (adjusted OR 1.31; 95% CI 0.78 to 2.20, p = 0.313). Mean costs per patient were £1217 with point-of-care versus £1006 with standard care (p = 0.056), while mean QALYs were 0.158 versus 0.161 (p = 0.250). The probability of standard care being dominant (i.e. cheaper and more effective) was 0.888. Point-of-care testing increases the proportion of patients successfully discharged home and reduces the median (but not mean) length of hospital stay. It is more expensive than standard care and unlikely to be considered cost-effective. Current Controlled Trials ISRCTN37823923. This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 15, No. 23. See the HTA programme website for further project information.